Clinical and histopathological study of a hollow and posteriorly multiperforated polymethylmethacrylate implant in eviscerated rabbit eyes - Silva,Marlos R Lopes e (2022)
ABSTRACT Purpose: The study aimed to evaluate the clinical and tissue response to a hollow polymethylmethacrylate orbital implant with a multiperforated posterior surface in an animal model after evisceration. Methods: Sixteen New Zealand rabbits had their right eye eviscerated. All animals received a hollow polymethylmethacrylate implant 12 mm in diameter that is multiperforated in its posterior hemisphere. The animals were divided into four groups, and each one had the eye exenterated at 7, 30, 90, and 180 days post-evisceration. Clinical signs were assessed daily for 14 days post-evisceration and then every 7 days until 180 days. Inflammatory pattern, collagen structure, and degree of neovascularization generated with implant placement were analyzed with hematoxylin-eosin, picrosirius red, and immunohistochemistry staining. Results: There were no signs of infection, conjunctival or scleral thinning, or implant exposure or extrusion in any animal during the study. On day 7, the new tissue migrated into the implant and formed a fibrovascular network through the posterior channels. Inflammatory response reduced over time, and no multinucleated giant cells were found at any time. Conclusion: Hollow polymethylmethacrylate orbital implants with a multiperforated posterior surface enable rapid integration with orbital tissues by fibrovascular ingrowth. We believe that this orbital implant model can be used in research on humans.